The landscape of research on B cell and immunotherapy in solid tumors over the past 20 years - Shuman Kuang; Mingjian Piao; Chengjie Li; Nan Zhang; Jiongyuan Li; Shuofeng Li; Binhe Tian; Lijin Zhao; Haitao Zhao (Discover Oncology)
Abstract Background Immunotherapy, remarkably immune checkpoint inhibitors, has shown significant efficacy and survival benefits in patients with various solid tumors. Although T lymphocytes have been extensively studied as the primary target cells, the role and application of B cells in solid tumor immunotherapy remain less understood. Methods In this study, we conducted a bibliometric analysis of articles on solid tumor immunotherapy related to B cells, published from 2003 to March 28, 2024, in the Web of Science Core Collection. Co-authorship and keyword co-occurrence analyses were performed using VOSviewer, while CiteSpace was used to identify burst keywords and references. Results A total of 1995 publications were analyzed, revealing a year-on-year increase in articles. The most common keywords are “immunotherapy” and “expression”. The most frequently referenced publications focused on tertiary lymphoid structures and B-cell markers. The United States and China are the largest contributors to this field, with Frontiers in Immunology being the most prolific journal. This study provides a comprehensive overview of over 20 years of B cell and immunotherapy research in solid tumors, identifying key countries, institutions, authors, journals, and publications. Conclusions The findings offer valuable insights into the relationship between B cells and immunotherapy in solid tumors. This study primarily unveils the current research hotspots concerning the role of B cells in immunotherapy, encompassing both fundamental research and clinical trials, as well as the accelerating emergence of an increasing number of B-cell-centric immunotherapies.